The association between HPV vaccination and new-onset cardiovascular and cerebrovascular diseases: based on a retrospective study - Chiao-Yu Yang; Yu-Hsiang Shih; Chia-Chi Lung (Journal of Health, Population and Nutrition)
Abstract Introduction Human papillomavirus (HPV), a widespread sexually transmitted infection, is well-known for its association with cancers like cervical, anal, and oropharyngeal. While extensively studied for its oncogenic properties, HPV’s influence on these non-cancerous conditions remains under investigation. This study examines the impact of HPV vaccination on the incidence of cardiovascular and cerebrovascular diseases, exploring its protective potential. Methods Utilizing the global TriNetX database, this retrospective cohort study analyzed data from adults aged 20 to 40 who were either vaccinated or not vaccinated against HPV between January 1, 2019, and December 31, 2021. The study employed propensity score matching to ensure balanced comparison groups and utilized ICD-10 codes to identify new-onset cardiovascular and cerebrovascular diseases. Results The study included 59,423 vaccinated and an equal number of unvaccinated individuals, balanced for various demographic and health characteristics. The vaccinated group demonstrated a lower incidence of cardiovascular diseases (hazard ratio [HR] = 0.9, 95% CI 0.847–0.957), cerebrovascular diseases (HR = 0.605, 95% CI 0.484–0.754), and heart dysfunction (HR = 0.833, 95% CI 0.708–0.98) compared to the unvaccinated group. Subgroup analyses further supported the protective effect of HPV vaccination across different demographics. Conclusion HPV vaccination is linked to a lower risk of new-onset cardiovascular and cerebrovascular diseases in adults, suggesting broader health benefits beyond cancer prevention. These results advocate for incorporating cardiovascular health into public health strategies promoting HPV vaccination. Further research is necessary to understand the mechanisms and validate these protective effects across diverse populations and extended follow-up periods.